Health-promoting lifestyle y assertiveness in university workers - Jiménez Bernardino, Ernesto; Álvarez Aguirre, Alicia; Reyes Rocha, Blanca Lilia; Casique Casique, Leticia; Herrera Paredes, José Manuel; Sánchez Perales, Mercedes (Investigación y Educación en Enfermería, 2017)
Objective. The work sought to analyze the health-promoting lifestyle variables, assertiveness, and their relation to health condition in university workers. Methods. This was a correlational study with the participation of 112 workers selected through census-type random sampling. To gather information, a form was used that included sociodemographic, anthropometric, and clinical data, in addition to the health-promoting lifestyle scale by Walker et al., and the Assertiveness Questionnaire by Lazarus and Folkman. Results. Participants ranged between 24 and 72 years of age (mean = 45), 61.6% were women, 49.1% worked the day shift, and 59.8% worked as teaching staff. With respect to health problems diagnosed: 17.0% had high blood pressure, 4.5% type II diabetes mellitus, and 4.5% suffer both diseases; 46.4% were found with overweight condition and 23.9% with some degree of obesity. The general index of health-promoting lifestyle was of 39.2 points (medium level) and assertiveness of 74.5 points (high level). A positive and significant relationship was found between assertiveness and the general index of the health-promoting lifestyle (r = 0.22, p <0.05) and the dimensions of spiritual development (r = 0.35, p<0.01) and interpersonal relations (r = 0.29, p <0.01). Likewise, glucose level, one of the parameters of the health condition, was inversely related to the health-promoting lifestyle (r = -0.20, p <0.05) and to the dimensions of physical activity (r = -0.24, p <0.01) and stress management (r = -0.24, p <0.01). Conclusion. The findings show the relationship between the health-promoting lifestyle and assertiveness in university workers studied, which justifies the design of educational interventions from nursing aimed at improving these aspects. How to cite this article: Jiménez E, Álvarez A, Reyes BL, Casique L, Herrera JM, Sánchez M. Health-promoting lifestyle and assertiveness in university workers. Invest. Educ. Enferm. 2017; 35(1):